Classical mechanics : lecture notes - Likharev, K. K. (Konstantin Konstantinovich) (IOP (Series). Release 4., 2017)
Essential Advanced Physics' is a series comprising four parts: 'Classical Mechanics', 'Classical Electrodynamics', 'Quantum Mechanics' and 'Statistical Mechanics'. Each part consists of two volumes, Lecture Notes and Problems with Solutions, further supplemented by an additional collection of test problems and solutions available to qualifying university instructors. This volume, 'Classical Mechanics: Lecture Notes', is intended to be the basis for a one-semester graduate-level course on classical mechanics and dynamics, including the mechanics of continua, in particular deformations, elasticity, waves, and fluid dynamics.